2011
DOI: 10.1111/j.1601-0825.2011.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokine levels in hyperlipidemic patients with periodontitis after periodontal treatment

Abstract: The combination of the periodontal therapy and antilipemic treatment may provide beneficial effects on the metabolic and inflammatory control of hyperlipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 51 publications
5
64
0
Order By: Relevance
“…These findings may also favor an affirmative relationship between serum lipids and periodontal tissue response or vice-versa and are in line with aforementioned studies. 10,22,26,27,29,31,56 In the present study, age, number of missing teeth and BMI were significantly higher in the hyperlipidemic group compared to the normolipidemic group. The finding of revealed number of missing teeth was consistent with the assumption stating association between periodontal disease progression and serum lipid levels.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…These findings may also favor an affirmative relationship between serum lipids and periodontal tissue response or vice-versa and are in line with aforementioned studies. 10,22,26,27,29,31,56 In the present study, age, number of missing teeth and BMI were significantly higher in the hyperlipidemic group compared to the normolipidemic group. The finding of revealed number of missing teeth was consistent with the assumption stating association between periodontal disease progression and serum lipid levels.…”
Section: Discussionsupporting
confidence: 46%
“…The comparisons of periodontal clinical parameters between normolipidemic individuals and hyperlipidemic patients showed that PD, BOP, CAL and CPITN in the hyperlipidemic group were significantly higher compared with normolipidemic group. This result demonstrates that patients with hyperlipidemia may have a pronounced tissue response and show a high rate periodontal disease susceptibility than those who are normolipidemic, 10,22,26,27,29,31,56 although PI and GI of the groups were similar. Hence, the similarity in the oral hygiene regimens of the groups by means of brushing/interdental cleaning is of importance in creation a homogeneous population necessary for true assessment of any relationship between periodontal disease and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Overall, LPO products lead to increased immune response, fibrosis or inflammation, inactivation of thiol-containing enzymes, gene transcription, or triggered apoptosis due to higher molecular activity, and are associated with CVD (11). The role of LPO in CVD and periodontitis has been confirmed by studies examining the association between periodontitis and impaired lipid metabolism (5,40,41). Increased LPO in serum and periodontal tissue was observed in case of experimental periodontitis (42).…”
Section: Discussionmentioning
confidence: 97%
“…This type of diet can result in plaque accumulation [35]. Overconsumption of high-fat foods induced by stress can lead to increased cortisol production and thus immunosuppression [35,37]. Any changes to diet can cause stress and can be a risk factor for periodontal disease [25,35].…”
Section: Changes To Dietmentioning
confidence: 99%